Dynamics of waqf in the city of Langsa (Case Study of Understanding Religious Figures) - fatah, Fatahillah; Anwar Puteh (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Purpose – to reveal and explain the dynamics of waqf in Langsa City starting from waqf regulation, public understanding, and understanding of Langsa City religious leaders. Method – This research uses a descriptive method with a qualitative approach with primary and secondary data. Data collection methods used by observation, interviews, and documentation. This study can find that the community and religious leaders in Langsa City use the Syafi'i school of jurisprudence in the legal basis, including waqf. Research Results - The results of this study related to the polemic of understanding religious leaders in Langsa City is because Aceh has its own fatwa institution not under the central MUI institution and Aceh's MPU so far has not issued a fatwa related to whether or not the practice of cash waqf is allowed. In this case, the researcher sees that if the Aceh MPU issues a regulation or fatwa regarding the permissible practice of cash waqf, then the harmony of understanding of religious leaders in Aceh, especially Langsa City will be reconciled over time. Practical Implications – As a practical implication, the results of this study can be used as a reference by the government, especially waqf organizations.